The biomechanics of running in athletes with previous hamstring injury: A case‐control study. Issue 4 (27th April 2015) - Daly, C.; McCarthy Persson, U.; Twycross‐Lewis, R.; Woledge, R. C.; Morrissey, D.
Abstract : Hamstring injury is prevalent with persistently high reinjury rates. We aim to inform hamstring rehabilitation by exploring the electromyographic and kinematic characteristics of running in athletes with previous hamstring injury. Nine elite male Gaelic games athletes who had returned to sport after hamstring injury and eight closely matched controls sprinted while lower limb kinematics and muscle activity of the previously injured biceps femoris, bilateral gluteus maximus, lumbar erector spinae, rectus femoris, and external oblique were recorded. Intergroup comparisons of muscle activation ratios and kinematics were performed. Previously injured athletes demonstrated significantly reduced biceps femoris muscle activation ratios with respect to ipsilateral gluteus maximus (maximum difference −12.5%, P = 0.03), ipsilateral erector spinae (maximum difference −12.5%, P = 0.01), ipsilateral external oblique (maximum difference −23%, P = 0.01), and contralateral rectus femoris (maximum difference −22%, P = 0.02) in the late swing phase. We also detected sagittal asymmetry in hip flexion (maximum 8°, P = 0.01), pelvic tilt (maximum 4°, P = 0.02), and medial rotation of the knee (maximum 6°, P = 0.03) effectively putting the hamstrings in a lengthened position just before heel strike. Previous hamstring injury is associated with altered biceps femoris associated muscle activity and potentially injurious kinematics. These deficits should be considered and addressed during rehabilitation.